Approach to undiagnosed exudative pleural effusion: the diagnostic yield of blind pleural biopsy - Solooki, Mehrdad (Babol University of Medical Sciences, 2013)
Background: Blind percutaneous pleural biopsy has traditionally been performed to investigate the etiology of exudative pleural effusion in which the initial thoracocentesis has been non- diagnostic. In view of the increasing use of image-guided and thoracoscopic pleural biopsies, this study examined the role of blind Abrams pleural biopsy in the investigation of the exudative pleural effusion in the largest tertiary pulmonary center in Tehran, Iran. Methods: All patients with pleural effusion admitted from September 2007 to April 2009 entered in this study. The patients with exudative pleural effusion underwent blind Abrams pleural biopsy when the initial thoracocentesis was non-diagnostic. The patients with non-diagnostic blind biopsy underwent surgical biopsy or other investigations based on the physician’s decision. The data were collected and analyzed. Results: Blind percutaneous pleural biopsy was performed in 171 patients. Malignancy was diagnosed in 56 and tuberculosis in 52 cases with blind biopsy. For all the diagnoses, blind biopsy had a sensitivity of 70.1% and negative predictive value of 14.8%. For malignant diagnosis, the sensitivity value was 58.9%, specificity 100% and negative predictive value 63.2%. For TB diagnosis, sensitivity value was 88.1%, specificity 100% and negative predictive value 93.6%. The overall malignancy was diagnosed in 95 (58.6%) and TB in 59 (36.4%) patients. Conclusion: Blind Abrams needle biopsy was diagnostic in approximately three out four patients presented with undiagnosed exudative pleural effusion. The data support the use of the Abrams needle in the investigation of pleural effusion especially in the less developed countries.